Transformasi Digital dalam Administrasi Publik Strategi Peningkatan Efisiensi dan Transparansi Layanan Pemerintah di Kabupaten Poso - Herlan Lagantondo; Abdi Sakti Walenta (Jurnal Media Administrasi, 2026)
This study aims to analyze digital transformation in public administration as a strategy to improve the efficiency and transparency of government services in Poso Regency. The study uses a qualitative approach with library research methods, sourced from various scientific literature, both national and international journals relevant to the research topic. The results show that digital transformation plays a significant role in improving the efficiency of public services through the automation of administrative processes, thereby accelerating service times and reducing the potential for human error. Furthermore, digital transformation also increases transparency and accountability through the openness of public information that is widely accessible to the public. However, the implementation of digital transformation in the regions still faces various challenges, such as limited technological infrastructure, low readiness and competence of human resources, and suboptimal system integration and data security. Therefore, a comprehensive strategy is needed, including strengthening digital infrastructure, increasing the capacity of government officials, and optimizing open data-based policies. This research is expected to contribute to the development of sustainable digital transformation policies at the regional level.